Synthesis and Optoelectrochemical Properties of Stilbenophanes Having Carbazole Moieties - Rajakumar, Perumal; Sekar, Karuppannan; Venkatesan, Nagarathinam (Synlett, 2012)
A series of stilbenophanes having N-arylated carbazole moieties possessing small and large cavities have been synthesized via McMurry coupling of the corresponding dialdehyde derived from N-arylation of carbazole with various dibromide followed by formylation. The electrochemical, photophysical, and complexation properties of all the stilbenophanes with electron-deficient guest molecules like TCNQ, TCNE, and PQT were also carried out at different concentrations.
Keywords: carbazole; stilbenophanes; fluorescence; redox potential